TRADISI MANDI BALIMAU KASAI DI DESA BATU BELAH KEC. BANGKINANG KAB. KAMPAR PROV. RIAU: Tinjauan Historis Hingga Dampaknya Bagi Masyarakat - Wulandari, Suri; Pane, Ismail (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
One of the traditions that has survived to this day in the area of Stone Belah Kec by Kab. Kampar is the tradition of the Balimau Kasai bath that is performed in the month of Ramadan with the aim of purifying yourself. This study examines specifically the Balimau Kasai bathing tradition in the village of Stone Belah, reviewing the historicity of the tradition and its impact on society. The research method used is qualitative-descriptive, with the collection of data from live interviews and sources from books, journals, and articles related to the dissemination of research. The results showed that the Balimau Kasai bathing tradition was carried out by Muslim society in line with the arrival of Islam, and the influence of Islam was felt in Kampar in the 14th century. So the tradition of bathing Balimau Kasai is one of the traditions resulting from the harmonization between custom, the elements of old beliefs (Hindu and Buddhist), and the teachings of Islam. Regarding the implementation of the tradition in accordance with the previous generations, which is to boil the purple lemon, pack the kasai limon, make traditional food, and slaughter the kerbau, bring the rantang containing the limon that has been packed with kasai and the ranting that contains the ninik mamak food to the house of relatives, get limon money, have Asar prayer in the mosque for men, and further bathe in the Kampar River, and the last celebration. Today, the series of practices begins with the donation to the orphans, then the delivery of religious material, and finally the feast of the banana. As for the impact of the implementation of the Balimau Kasai bathing tradition on society, it is the strengthening of Islamic values, the development of cultural tourism, the movement of the economy of the community, and the deviation of values.